Using gastrointestinal distress reports to predict youth anxiety risk: Implications for mental health literacy and community care. Issue 6 (4th May 2021) - Bloom, Paul Alexander; Douglas, Ian; VanTieghem, Michelle; Tottenham, Nim; Callaghan, Bridget
Abstract: This study investigates the generalizability and predictive validity of associations between gastrointestinal (GI) symptoms and youth anxiety to establish their utility in community mental health decision‐making. We analyzed data from youth ages 3 to 21 years in volunteer cohorts collected in Los Angeles (N = 327) and New York City (N = 102), as well as the Healthy Brain Network cohort (N = 1957). Youth GI distress was measured through items taken from the parent‐reported Child Behavior Checklist (CBCL). We examined generalizability of GI–anxiety associations across cohorts and anxiety reporters, then evaluated the performance of these models in predicting youth anxiety in holdout data. Consistent with previous work, higher levels of gastrointestinal distress were associated with more parent‐reported youth anxiety behaviors in all three cohorts. Models trained on data from the Healthy Brain Network cohort predicted parent‐reported and child‐reported anxiety behaviors, as well as clinician‐evaluated anxiety diagnoses, at above chance levels in holdout data. Models which included GI symptoms often, but not always, outperformed models based on age and sex alone in predicting youth anxiety. Based on the generalizability and predictive validity of GI–anxiety associations investigated here, GI symptoms may be an effective tool for child‐facing professionals for identifying children at risk for anxiety (Preprint: https://psyarxiv.com/zgavu/ ).